Adjuvant doxorubicin vs metronomic cyclophosphamide and meloxicam vs surgery alone for cats with mammary carcinomas: A retrospective study of 137 cases. (9th November 2020) - Petrucci, Gonçalo N.; Henriques, Joaquim; Lobo, Luís; Vilhena, Hugo; Figueira, Ana C.; Canadas‐Sousa, Ana; Dias‐Pereira, Patrícia; Prada, Justina; Pires, Isabel; Queiroga, Felisbina L.
Abstract: This study aims to evaluate the efficacy and side effects of low dose cyclophosphamide chemotherapy plus meloxicam as an adjuvant treatment, compared with high dose doxorubicin or surgery alone in cats with mammary carcinoma. Medical records of 228 female cats treated for mammary carcinoma between 2008 and 2018, were reviewed in eight veterinary institutions. Only cats with complete tumour staging and radical mastectomy were included in the study. One hundred and thirty‐seven cats were divided into three treatment groups: group 1 (n = 80) cats treated with surgery, group 2 (n = 34) cats that had surgery and adjuvant treatment with doxorubicin, and group 3 (n = 23) cats with surgery and adjuvant treatment with low dose metronomic cyclophosphamide and meloxicam. The study endpoints were disease free interval (DFI) and overall survival (OS). Toxicity was evaluated according to the VCOG‐CTCAE criteria. The median DFI was 270, 226 and 372 days in groups 1, 2 and 3, respectively. The median OS was 338 (group 1), 421 (group 2) and 430 (group 3) days. The differences between groups were not significant (DFI P  = .280 and OS P  = .186). Toxicity was observed in 52.9% (n = 18) of cats in group 2 and 39.1% (n = 9) of cats in group 3, with mild to moderate intensity. Differences were not significant ( P  = .306). In conclusion, adjuvant chemotherapy treatment did not improve survival and the overall benefit remains unproven. Randomized prospective trials are necessary to clarify the effectiveness of adjuvant chemotherapy treatment for feline mammary carcinomas.